Early Life Events can Shape Aging and Longevity - Bartke, Andrzej (Current Aging Science, 2015)
There is increasing evidence that nutritional and hormonal signals during development can influence longevity. It was reported that mice subjected to mild calorie restriction only during the preweaning period live longer than control animals. In long-lived hypopituitary dwarf mice, longevity can be reduced by growth hormone replacement therapy during pre- and peri-pubertal period. These findings suggest that trajectory of aging is importantly influenced by the availability of nutrients and the levels of anabolic hormones during development.
Keywords: calorie restriction